Factors and barriers to sulfadoxine-pyrimethamine uptake for intermittent preventive treatment during pregnancy in Ghana - Akua Kumi Yeboah; Patrick Ohemeng Gyaase; Richmond Bediako Nsiah; Regina Amoa-Tutu; Saida Abdul-Rahman Zakaria; Lynna Naa Adede Obeng; Frank Prempeh; Phenihas Kwadwo Opoku; Amos Andoono; Gilbert Elara Dagoe; Kwame Kusi Agyemang; Jonathan Mawutor Gmanyami; et al. (Academia Medicine)
Malaria continues to pose a significant threat to pregnant women in sub-Saharan Africa, including Ghana, where the uptake of intermittent preventive treatment in pregnancy with sulfadoxine-pyrimethamine (IPTp-SP) remains below optimal levels. This study explored factors influencing IPTp-SP uptake among 300 postpartum mothers in Asunafo North Municipal using a descriptive cross-sectional design. Data were gathered through pretested questionnaires, and statistical analyses included descriptive, bivariate, and multivariate methods, with logistic regression used to assess relationships at a significance level of α = 0.05. A significant proportion (43.7%) of participants received three or more doses of IPTp-SP, while 56.3% received two or fewer doses. Key barriers to uptake included being unmarried (AOR = 0.36, [95% CI 0.145–0.881], p = 0.025) and unemployed (COR = 0.61, [95% CI 0.38–0.98], p = 0.042). Fewer antenatal care (ANC) visits (≤3 times) were strongly associated with lower odds of receiving three or more doses (AOR = 0.03, [95% CI 0.01–0.83], p < 0.001). Higher IPTp-SP uptake was positively linked to the perceived severity of malaria in pregnancy (AOR = 0.19, [95% CI 1.02–4.20], p = 0.045) and the perceived benefits of IPTp-SP (AOR = 0.39, [95% CI 0.19–0.78], p = 0.008). Perceived susceptibility to malaria did not significantly affect uptake. Sociodemographic factors such as age, education, and parity showed no significant associations. Major barriers included time and financial constraints related to ANC attendance. The study underscores the need for better alignment between ANC attendance and IPTp-SP administration, and suggests that future research should evaluate ANC interventions to enhance IPTp-SP uptake and reduce malaria-related complications.